Giving voices to multimodal applications - Almeida, N.; Teixeira, A.; Rosa, A.F.; Braga, D.; Freitas, J.; Dias, J.; Silva, S.; Avelar, J.; Chesi, C.; Saldanha, N (Human-computer interaction: Interaction technologies: 17th International Conference, HCI International 2015, Los Angeles, CA, USA, August 2–7, 2015, Proceedings, 2015)
The use of speech interaction is important and useful in a wide range of applications. It is a natural way of interaction and it is easy to use by people in general. The development of speech enabled applications is a big challenge that increases if several languages are required, a common scenario, for example, in Europe. Tackling this challenge requires the proposal of methods and tools that foster easier deployment of speech features, harnessing developers with versatile means to include speech interaction in their applications. Besides, only a reduced variety of voices are available (sometimes only one per language) which raises problems regarding the fulfillment of user preferences and hinders a deeper exploration regarding voices’ adequacy to specific applications and users. 17th International Conference, HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings, Part II Part of the Lecture Notes in Computer Science book series (LNCS, volume 9170) Also part of the Information Systems and Applications, incl. Internet/Web, and HCI book sub series (LNISA, volume 9170)